Peran Pendidikan Agama Katolik Dalam Pembentukan Karakter Religius Peserta Didik Di SMPN 2 Malinau Utara - X, Intansakti Pius (SAPA - Jurnal Kateketik dan Pastoral, 2020)
English: This research is motivated by the reality of the lives of students who are heavily influenced by the times, which results in changes in attitudes, mental and behavior in an unfavorable direction. Catholic Religious Education is expected to be able to deliver students to be more Christian in faith and to build loyalty to the faith in Jesus Christ. The fact that what happened was, students at SMPN 2 Malinau Utara found it difficult to get involved in church activities, increased violence between friends, did not pay attention to environmental cleanliness, and satire on social media. The formulation of the problem in this study is the extent to which Catholic Religious Education plays a role in the formation of religious character at SMPN 2 Malinau Utara. The research design was descriptive quantitative. The data collection instrument was a questionnaire. The research subjects consisted of teachers and parents. The population in this study were all Catholic students at SMPN 2 Malinau Utara class VII to class IX. Data processing using F percent, scoring, and chi squared to analyze and describe the data. The results of the study proved to reject the null hypothesis, and accept the alternative hypothesis which states that the role of Catholic Religious Education in the formation of Participant Religious character at SMPN 2 Malinau Utara is quite good. These results are in accordance with the results of the overall data processing using scoring, where the score was 2.393. Indonesia: Penelitian ini dilatarbelakangi oleh realitas hidup peserta didik yang banyak dipengaruhi oleh perkembangan zaman, yang mengakibatkan adanya perubahan sikap, mental maupun tingkah laku ke arah yang kurang baik. Pendidikan Agama Katolik diharapkan mampu menghantar peserta didik semakin beriman kristiani dan membangun kesetiaan pada iman akan Yesus Kristus. Fakta yang terjadi adalah, peserta didik di SMPN 2 Malinau Utara sulit terlibat dalam kegiatan gereja, meningkatnya tindak kekerasan antarteman, kurang memperhatikan kebersihan lingkungan, serta saling sindir lewat media sosial. Rumusan masalah dalam penelitian ini adalah, sejauh mana Pendidikan Agama Katolik berperan dalam pembentukan karakter religius di SMPN 2 Malinau Utara. Rancangan penelitian adalah deskriptif kuantitatif. Instrumen pengumpul data berupa angket. Subyek penelitian terdiri dari para guru dan wali murid. Populasi dalam penelitian ini adalah seluruh peserta didik yang beragama Katolik di SMPN 2 Malinau Utara kelas VII sampai kelas IX. Pengolahan data menggunakan F persen, scoring, dan chi kuadrat untuk menganalisa dan mendeskripsikan data. Hasil penelitian terbukti menolak hipotesa nol, dan menerima hipotesa alternatif yang menyatakan bahwa peran Pendidikan Agama Katolik dalam pembentukan karakter Religius Peserta di SMPN 2 Malinau Utara cukup baik. Hasil ini sesuai dengan hasil pengolahan data secara keseluruhan menggunakan scoring, dimana diperoleh skor sebesar 2,393.